The b-chromatic number of certain graphs and digraphs. (3rd March 2016) - Kok, Johan; Sudev, N. K.
Abstract: The b -chromatic number of a graph G is the maximum number k of colours in a proper colouring of G, such that at least one vertex in each colour class has a neighbour in all other classes. In this paper, we discuss the b -chromatic number of certain classes of graphs and digraphs.